Characteristics and mechanisms of hydrogen-induced quasi-cleavage fracture of lath martensitic steel. (March 2021) - Cho, L.; Bradley, P.E.; Lauria, D.S.; Martin, M.L.; Connolly, M.J.; Benzing, J.T.; Seo, E.J.; Findley, K.O.; Speer, J.G.; Slifka, A.J.
Abstract: This study presents an in-depth characterization of the microstructures, crystallographic orientations, and dislocation characteristics beneath hydrogen-induced quasi-cleavage fracture features of an as-quenched, lath martensitic (α') 22MnB5 steel. The fracture surfaces of gaseous hydrogen-embrittled martensitic specimens were analyzed by a combination of multiple analytical tools: scanning electron microscopy (SEM), electron backscatter diffraction (EBSD), transmission electron microscopy (TEM), and transmission Kikuchi diffraction (TKD). The dominant fracture mode in the hydrogen-affected zones was quasi-cleavage fracture, which involved significant plasticity, evidenced by plastic zones near tear ridges and a high density of dislocations beneath the quasi-cleavage facets. The martensite constituent sizes, variant orientations, and boundaries influenced the quasi-cleavage surface morphologies. Fractography revealed the occurrence of {100}α' -type cleavage across martensitic laths, developing relatively "flat" quasi-cleavage surfaces, in addition to {110}α' -type cracking likely along lath and block boundaries, and fracture along non-cleavage planes. The likelihood of the formation of the relatively "flat" quasi-cleavage surfaces increased with increasing martensitic constituent sizes. Substantial dislocation bands formed on intersecting {112}α' slip planes within a martensite block below the hydrogen-induced cleavage fractures on {100}α' planes. River markings on the quasi-cleavage surfaces were found to originate from the complex, hierarchical lath martensitic microstructure. Steps and ridges on the quasi-cleavage facets generally linked with the various martensitic boundaries, suggesting that they were produced as a result of crack deviations at those boundaries. The fracture paths and martensite quasi-cleavage mechanisms are discussed in the context of the role of hydrogen and Cottrell cleavage model. Graphical abstract: Image, graphical abstract